Comparing Different Routes of Vitamin D Administration: A Randomized Interventional Trial - Jamal Ara; Aneela Altaf Kidwai; Saleem Aminullah Paracha; Nooruddin Sadaruddin; Farah Asad; Amna Begum (ziauddin University, 2020)
Background: Vitamin D maintains overall good health by boosting up of the immune system through proper function of lungs, heart, muscles, brain and bones. The goal of the study was to determine and compare different routes and formulation of vitamin D3 that was per oral, injectable formulation given orally and intramuscular injection in patients of different groups. Methods: This was a randomized clinical trial designed for vitamin D deficient patients. Patients were randomly assigned to three routes of administration i.e. orally, injection formulation given orally andintramuscular injection group. For mild deficiency, 2 doses of 200,000 IU, for moderate deficiency, 3 doses of 200,000 IU and for severe deficiency, 4 doses of 200,000 IU, 25[OH] D was prescribed. Chi-Square (χ2 ) test was used to evaluate the significant association . Results: A total of 150 patients were enrolled in the study. The mean age ±SD of patients was 48.29 ± 4.65 years. At 4 and 12 weeks after completion of vitamin D3 replacement, levels of 25-hydroxycholecalciferol were measured. In the majority of participants of all three groups, the levels of vitamin D were increased to normal range by week 4 after the final dose of vitamin D3. However, the majority of patients failed to maintain their Vitamin D3 levels within the normal range 12 weeks after the final dose. All three routes of administration of Vitamin D were found equally effective with no significant difference between the routes (p>0.05). Conclusion: All three routes of administration of vitamin D supplements had equal efficacy with no significant advantage over one another.